ECO-FRIENDLY DIGITAL ENTREPRENEURSHIP MODEL FOR TOWARDS SUSTAINABILITY DEVELOPMENT - Muhammad Isa Indrawan; Hasrul Azwar Hasibuan; Elfitra Desy Surya (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2025)
The development of digital technology has driven a significant transformation in the world of entrepreneurship, not only in terms of innovation and efficiency, but also in the application of sustainability principles. The environmentally friendly digital entrepreneurship model is one of the strategic approaches to answer the challenges of the Industrial Revolution 4.0 era while supporting the achievement of the Sustainable Development Goals (SDGs). This research aims to identify and analyze key elements in the development of digital entrepreneurship models that combine technology, innovation, and environmentally friendly practices. The research method used is mixed methods by combining literature studies, quantitative surveys on digital business actors, and in-depth interviews with sustainability experts. The results show that the adoption of green technology, resource use efficiency, and circular economy-based innovation are the main factors in shaping a sustainable digital entrepreneurship model. In addition, government policy support, cross-sector collaboration, and consumer awareness of environmental issues strengthen the successful implementation of this model. These findings are expected to be a reference for business actors, policymakers, and academics in developing an inclusive, innovative, and environmentally friendly digital entrepreneurship ecosystem to realize sustainable development goals.